Need Analysis for Android-Based Interactive Media on Menstruation Material in Islamic Religious Education at SD Negeri 1 Gebang - Yuvita Nila Rahayu; Mashudi; Abd Muhith (ATTA`DIB, 2025)
Abstract Menstruation education in Islamic Religious Learning (IRL) at the elementary level remains a sensitive and often neglected topic due to cultural taboos and limited instructional resources. To address this, the study explores the need for Android-based interactive learning media to teach menstruation material in a more engaging and religiously appropriate way. This research employed a qualitative descriptive approach conducted at SD Negeri 1 Gebang. Data were collected through interviews, observations, and documentation involving Islamic education teachers and female fourth-grade students. Data analysis included reduction, categorization, display, and verification stages.Findings revealed that both teachers and students face challenges in discussing menstruation topics. Teachers lack digital teaching materials, while students experience discomfort and curiosity. The need analysis indicated that Android-based media featuring visual, audio, and interactive elements could increase engagement, understanding, and privacy while aligning with Islamic values.The study concludes that Android-based interactive media are highly needed to transform Islamic Religious Learning into a more inclusive and modern framework. Such media can bridge the gap between scientific understanding and religious teaching, making menstruation education more accessible, respectful, and effective for young Muslim girls. Keywords: Islamic Education, Android-Based Media, Menstruation, Need Analysis, Interactive Learning Abstrak Pembelajaran materi haid dalam Pendidikan Agama Islam (PAI) di tingkat sekolah dasar masih menjadi topik sensitif dan sering dihindari karena faktor budaya serta keterbatasan media pembelajaran. Penelitian ini bertujuan untuk menganalisis kebutuhan media pembelajaran interaktif berbasis Android dalam mengenalkan materi haid secara menarik dan sesuai nilai-nilai Islam. Penelitian ini menggunakan pendekatan kualitatif deskriptif yang dilaksanakan di SD Negeri 1 Gebang. Data dikumpulkan melalui wawancara, observasi, dan dokumentasi terhadap guru PAI dan siswi kelas IV. Analisis data dilakukan melalui tahap reduksi, kategorisasi, penyajian, dan verifikasi data. Hasil penelitian menunjukkan bahwa guru dan siswa mengalami kesulitan dalam membahas topik haid. Guru kekurangan bahan ajar digital, sedangkan siswi merasa malu dan ingin tahu. Analisis kebutuhan menunjukkan bahwa media berbasis Android dengan elemen visual, audio, dan interaktif dapat meningkatkan minat, pemahaman, serta menjaga privasi siswa dalam pembelajaran sesuai nilai Islam. Penelitian menyimpulkan bahwa media interaktif berbasis Android sangat dibutuhkan untuk mentransformasi pembelajaran PAI menjadi lebih inklusif dan modern, sekaligus menjembatani pemahaman ilmiah dan keagamaan dalam pendidikan haid bagi siswi Muslim. Kata Kunci: Pendidikan Agama Islam, Media Berbasis Android, Haid, Analisis Kebutuhan, Pembelajaran Interaktif.